2017
DOI: 10.1007/s11605-017-3410-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Approach to Improve the Prognosis in HCC Patients Via Decreasing Dissemination of EpCAM+ Circulating Tumor Cells

Abstract: Like the liver-directed therapies, AA can reduce the dissemination of CTCs, especially in patients with large-size HCC (>5 cm) and successively improve the early prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Moreover, in prior studies of the relationship between CTCs in postoperative peripheral blood and tumor recurrence, CTCs were commonly collected within 4–5 weeks after surgery. 27 , 28 Accordingly, we collected peripheral blood from HCC patients within 5 weeks after surgery to analyze the relationships between various CTC phenotypes and early recurrence. Our results further confirmed that postoperative mesenchymal CTCs were positively correlated with HCC recurrence and that the disease-free survival was significantly shortened in mesenchymal CTC-positive patients compared to mesenchymal CTC-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in prior studies of the relationship between CTCs in postoperative peripheral blood and tumor recurrence, CTCs were commonly collected within 4–5 weeks after surgery. 27 , 28 Accordingly, we collected peripheral blood from HCC patients within 5 weeks after surgery to analyze the relationships between various CTC phenotypes and early recurrence. Our results further confirmed that postoperative mesenchymal CTCs were positively correlated with HCC recurrence and that the disease-free survival was significantly shortened in mesenchymal CTC-positive patients compared to mesenchymal CTC-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggested that surgery-induced manipulation of the liver is associated with a release of CTCs [94]. A comparison between anterior and conventional surgical approaches suggested that the latter was associated with a higher release of CTCs as well as poorer outcomes [89]. Toso et al described five steps during orthotopic liver transplant (OLT) in HCC patients to minimize CTC dissemination and thereby the risk of recurrence [104].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Cancer cell dissemination seems to be promoted by treatment, in particular surgical therapies. Liver manipulation is associated with a release of CTCs [ 215 ] and the anterior as compared to the conventional surgical approach is associated with a lower release of CTCs as well as better survival [ 216 ]. In liver transplantation for HCC, five steps to minimize CTCs dissemination and thereby reduce the risk of recurrence have been described [ 217 ].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%